TIDAL MODEL IN THE CARE OF A PATIENT WITH BIPOLAR 1 DISORDER: A JOURNEY TO RECOVERY - Laurence Garcia; Daisy Palompon, (The Malaysian Journal of Nursing (MJN), 2012)
This study utilized the Tidal Model in the care of a patient with Bipolar 1 Disorder. It seeks to answer the queries on the assessment findings of a perticularpatientwith bipolardisorderutilizingthe Tidal Model in terms of Self Domain, World Domain, and Others Domain and explore how the patient attained certain sense of recovery using the Tidal Model. Utilizing the case study type ofresearch, a qualitative analysis was used in the care of a patient with Bipolar 1 Disorder. The study was conducted during a nine-day exposure at the Center for Behavioral Sciences in a tertiary hospital in Cebu, Philippines. The patient, in the Self domain, was able to identify problems practically, realizing the need to live a normallife and the ways on how to achieve it. She (the patient) was also able to identify ways to find satisfaction for those needs by herself. The needs of the patients were more on the physiological aspect and on how to properly manage her present ill condition so as to be able to manage it in the future. Being ab le to identify these needs would mean that the patient has given value to herself and the very important role she plays in her journey to recovery. The findings showed that the use of the proposed daily journal of the Tidal Model has provided a means to continuously assess the patient's condition in her own words. The author would like to recommend the use of the theory to patients with a medical condition so that a more insightfuljournal would be gathered and to ascertain if mental recovery and rehabilitation help alleviate a medical condition.